(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This paper examined the unique security challenges posed by digital media use among Nigerian journalists, and the remedies that help mitigate the fast-growing threats. The study employed exploratory research design, while using literature review as a research instrument. Analysis of secondary data gathered from reviewed literature, Internet resources, and library materials, form the basis for discussion of digital journalism practice in Nigeria, its pros and the subtleties of digital security challenges that largely constitute its cons. Digital security trends in Africa were examined, vis-à-vis the lag in preparedness of African nations, including Nigeria, to tackle these security concerns at a level similar to efforts in developed countries. Technology Acceptance Model (TAM) formed the theoretical framework for this study, with its Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) components. A third component, ‘Perceived Threat of Use’ was introduced in an adapted Technology Acceptance Model, to underscore the priority of use over the awareness of the scope of digital threats by Nigerian journalists. A line of discourse was also opened on the subject of the security threats that the media audience ‘indirectly’ pose. The following measures were thus recommended for the Nigerian journalists who form the focal point of this study: awareness of technology scope, technical support, personalised network, prompt action, and discreetness. Keywords: Digital Security, Journalism, Technology, Threat, Audience